MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEs) IN THE PHILIPPINES: AN ANALYSIS OF THEIR PROCUREMENT MANAGEMENT - Dimaporo, Huzaifah S.; Codas, Maria Stella G. (International Journal of Application on Economics and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to local economic development, particularly in rural areas like Sultan Naga Dimaporo, Lanao del Norte, Philippines. They create employment, support community growth, and enhance economic resilience. However, many MSMEs face challenges in procurement management, which can impact their efficiency and growth. This study examined procurement practices among MSMEs in the municipality, focusing on stock sourcing, negotiation, bidding strategies, and inventory control. Using a descriptive-correlational research design, data were gathered through surveys of MSME owners and employees. Analysis involved frequency counts, weighted mean, and Kendall’s Tau-b to determine relationships between procurement practices and business growth. Results revealed that most MSMEs are small sole proprietorships operating for over a decade. While basic procurement activities like comparing supplier prices are common, formal practices, such as written contracts or supplier evaluation are rare. Inventory control received more attention, with many businesses adjusting stock based on demand and managing supply timelines manually. A moderate but significant correlation was found between procurement practices, particularly inventory control, and business growth. The study concludes that improving procurement even through simple measures can enhance MSME competitiveness and sustainability. It recommends targeted capacity-building support to strengthen procurement capabilities in rural enterprises.